Relevance of geographical indications and designations of origin for the sustainable use of genetic resources - Larson, J. (2007)
This study provides a worldwide panorama of current trends in Geographical Indications (GIs) as they relate to biodiversity conservation and rural development, and their potential contributions to poverty, hunger alleviation and environmental goals. When peasant and indigenous producer organizations decide to participate in the marketplace with a product that is not generic, GIs can be useful in developing and consolidating a differentiated geographical identity and a reputation, building quality systems and providing governance to value chains based on local biological resources and traditional and innovative knowledge and practices. Challenges and opportunities facing small producers from developing and transformation countries are identified, based on the experience of two dozen GI cases from all continents.